Clinical value of peripheral blood microRNA detection in evaluation of SOX regimen as neoadjuvant chemotherapy for gastric cancer. Issue 4 (23rd November 2017) - Tan, Bibo; Li, Yong; Di, Yan; Fan, Liqiao; Zhao, Qun; Liu, Qingwei; Wang, Dong; Jia, Nan
Abstract : Background: Neoadjuvant chemotherapy has been widely applied in treating advanced gastric cancer (GC). However, little research has been conducted on evaluating the effect of neoadjuvant chemotherapy. Purpose of this study was to evaluate the effect of SOX regimen as neoadjuvant chemotherapy by detecting some microRNAs. Methods: Total 120 GC patients who had received neoadjuvant chemotherapy (SOX regimen) were recruited with 100 healthy participants as control contemporarily. Age and gender have no significant difference in both groups ( P  >   .05). The effect of chemotherapy was evaluated by the results of CT scan and surgery. Also, adverse effects of chemotherapy were documented. Peripheral blood of GC patients was collected twice: one day before chemotherapy and surgery, respectively, whereas healthy controls' peripheral blood was collected once. Quantitative real‐time PCR (qPCR) was utilized to detect expression of miR‐145, miR‐185, miR‐381, and miR‐195 of peripheral blood in both groups. Results: One hundred and twenty patients with advanced GC completed a total of 386 cycles of neoadjuvant chemotherapy with effective rate at 84.17% (101 of 120). Expression of miR‐145, miR‐185, and miR‐381 of patients with GC was lower than that in the control group before chemotherapy commence (all P  <   .05), while the expressions of miR‐145 and miR‐185 elevated noticeably in CG patients after neoadjuvant chemotherapy ( P  <   .05). The differences in the expression of miR‐145 and miR‐185 in advanced GC patients with different chemotherapy outcomes were detected. Conclusion: Patients with GC at advanced stages had aberrant miRs expressions. Detection of miR‐145 and miR‐185 expression may assist to predict effectiveness and adverse effects of SOX regimen as neoadjuvant chemotherapy.